(untitled) (Al-Aasar, 2025)
This research paper examines the growing phenomenon of Romanization in Oriental languages, with a specific focus on Urdu in the 21st century. The paper analyzes the historical context, contemporary applications, and the sociocultural implications of using the Roman script for a language traditionally written in the PersoArabic script. Through a critical evaluation of both scholarly literature and empirical evidence, this study aims to present a balanced assessment of the advantages and disadvantages of Romanized Urdu. The findings reveal that while Romanization facilitates digital communication and accessibility for nonnative speakers, it simultaneously raises concerns about cultural authenticity, semantic precision, and the preservation of linguistic heritage. The paper concludes that the continued adoption of Roman script for Urdu represents a complex linguistic evolution shaped by globalization, technological advancement, and changing cultural identities.